Pengaruh Biaya Pendidikan, Pelayanan Dan Fasilitas SMK Nurul Hikmah Pasar Kemis, Dalam Menarik Minat Peserta Didik Baru - Siti Suhaepiah; Zain Zainuddin; Luthfi Nuraini (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
This study aims to find out how the influence of education costs, services and facilities at Nurul Hikmah Pasar Kemis Vocational High School, in attracting new students' interest. The author conducted research on 91 new students at Nurul Hikmah Vocational School who were respondents using the slovin formula and the sampling technique used simple random sampling. The data analysis method used is Multiple Linear Regression with the help of SPSS. The results of data analysis in this study show that the cost of education has a significantly positive effect on attracting new students with a Tcount of 3,391, greater than a Ttable of 1,662. Service significantly does not have a direct effect on attracting new students' interest significantly. Facilities significantly have no direct effect on attracting new students' interest. Tcount is 0.546, which is smaller than Ttable 1.662. and value (sig=0.586 > 0.05). As well as the Cost of Education, Services and Facilities simultaneously influence the interest of new students significantly with fcount 4.310 > 3.101 ftable.